Lasers are Quantum by Generators? (Global Journal of Science Frontier Research, 2018)
It is customary to assume lasers as quantum generators. But this name does not correspond to the principle of their action. Such generators present the phased lattices and are subordinated to the known laws of radio engineering. Physics of the work of such generators describes the relationships of Manley-Rou.
Keywords: laser; quantum generator; the phased antenna array; the relationship of manley-rou